2011
DOI: 10.1128/jcm.00676-11
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Severe and Fatal Infections Due to Klebsiella pneumoniae in Two University Hospitals in France

Abstract: Severe infections caused by hypermucoviscous Klebsiella pneumoniae have been reported in Southeast Asian countries over the past several decades. This report shows their emergence in France, with 12 cases observed during a 2-year period in two university hospitals. Two clones (sequence type 86 [ST86] and ST380) of serotype K2 caused five rapidly fatal bacteremia cases, three of which were associated with pneumonia, whereas seven liver abscess cases were caused by K1 strains of ST23.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
147
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(160 citation statements)
references
References 18 publications
9
147
2
2
Order By: Relevance
“…One study characterizing HV K. pneumoniae strains isolated from 4 different continents found that these strains were almost exclusively K1 strains (93%), while the remaining minority were K2 strains (235), a finding consistent with results of previous studies (18,(236)(237)(238)(239)(240)(241). Interestingly, in one study, 27/28 of the K1 HV K. pneumoniae isolates belonged to the same clonal complex (CC23), while the two K2 HV strains examined were genetically unrelated and arose from two distinct clonal lineages (ST25 and ST86) (235).…”
Section: Capsulesupporting
confidence: 81%
“…One study characterizing HV K. pneumoniae strains isolated from 4 different continents found that these strains were almost exclusively K1 strains (93%), while the remaining minority were K2 strains (235), a finding consistent with results of previous studies (18,(236)(237)(238)(239)(240)(241). Interestingly, in one study, 27/28 of the K1 HV K. pneumoniae isolates belonged to the same clonal complex (CC23), while the two K2 HV strains examined were genetically unrelated and arose from two distinct clonal lineages (ST25 and ST86) (235).…”
Section: Capsulesupporting
confidence: 81%
“…17 With this in mind, it is of great concern that 11 fatal cases in one clinical center were connected to CRKP28 as well as 5 deaths in France. 29 In 2004, the intrinsic contamination of a 2% chlorhexidine hand soap with K. pneumonia was reported. 30 In the current study, K. pneumonia was the most prominent pathogen cultured pre-cleaning (22 of the total of 50 cases) and 13 (59.1%) were resistant to chlorhexidine.…”
Section: Pathogen (N) Antibiotic Resistant Cases (N)mentioning
confidence: 99%
“…1,23,24,27,31 Resistance to the more commonly used antimicrobials equates to the following with number of pathogens out of the total of 113 indicated in brackets: ampicillin (20), amoxicillin-clavulanic acid (25), cefuroxime (18), cotrimoxazole (29) and erythromycin (14).…”
Section: Pathogen (N) Antibiotic Resistant Cases (N)mentioning
confidence: 99%
“…It initially manifested as the cause of community-acquired primary liver abscesses, sometimes complicated by metastatic meningitis and/or endophthalmitis, and it has been described by numerous investigators in Asian countries (1). Sporadic cases of severe infections have been reported throughout the world and are now increasingly recognized in Western countries (2)(3)(4)(5)(6)(7). The reasons for this epidemiological change and global differences remain unexplained.…”
mentioning
confidence: 99%